Encyclopedia of the solar system (Academic Press, 1999)
Written by more than 50 leading experts from around the world, the book provides an comprehensive overview of solar system science, including the Sun, the Earth and the eight other major planets, the Moon and other natural satellies, planetary rings, comets, asteroids, meteorites, and interplanetary dust.. It also discusses the dynamics of the solar system and planetary exploration missions